A great mimicker of mastoiditis: Multisystem Langerhans’ cell histiocytosis - Seong Kin, Foong; Cheng Ai, Ong; Arbaeyah Hussain, Faezahtul; Bee See, Goh (ENT Updates, 2020)
Langerhans’ cell histiocytosis (LCH) is a rare group of diseases characterized by abnormal clonal proliferation of Langerhans cells in one or more systems. LCH can occur in any system. We report a case of bilateral otologic LCH that presented as a case of mastoiditis. Despite multiple courses of antibiotics, there was no improvement. Subsequent excision biopsy of a postauricular mass confirmed the diagnosis of LCH. The patient responded well to chemotherapy